Project document revision - IICA, Roseau (Dominica) (2021)
IICA was formally engaged by UNDP through a LOA to manage the implementation of Output 2 of a project titled "Strengthening Disaster Management Capacity of Women in the Cooperative Republic of Guyana and Commonwealth of Dominica"The Output will be geared towards making targeted agricultural livelihoods more sustainable and less vulnerable to the impacts of CC. Major concerns are expressed from the hazard-prone farming communities in both countries about the lack of sustainable livelihoods to build resilience to the loss of farming income.